Penerapan Evidence Based Practice Nursing (EBPN) Modifikasi Miring Kiri dan Miring Kanan Menurunkan Back Pain Post Percutaneous Coronary Intervention (Journal of Telenursing (JOTING), 2023)
This study aims to apply the identification of left and right oblique modifications to reduce back pain after percutaneous coronary intervention based on the results of Evidence-Based Practice Nursing (EBPN) research. The research method used is a case study. The case study in this innovative design is a case study by applying research results in identifying left and right oblique modifications to reduce back pain post-percutaneous coronary intervention. The results showed that adjusting the correct oblique and left diagonal positions was carried out after two hours of cardiac catheterization, namely for 30 minutes (15 minutes in the correct oblique position and 15 minutes in the left oblique position). In conclusion, giving accurate diagonal left oblique work is carried out in patients who experience post PCI back pain at the time of the study, having a pain scale of 5. After being given intervention, the pain scale is reduced to 3. Keywords: PCI, PJK, Right and Left Tilt Position